IMPLEMENTASI SISTEM MANAJEMEN MUTU ISO 9001 : 2000 PADA SMK NEGERI 2 WONOGIRI - DIKIN , DIKIN (2011)
One of the standards of quality management mechanisms of the most prominent today is the quality management standard ISO 9001:2000. The success of the ISO 9001:2000 quality management system in improving the effectiveness and efficiency and the development of quality in the industrial sector offers opportunities for education to implement a quality management system into its scope. This research has the goal of describing the implementation and application of quality management system ISO 9001-2000 at SMK Negeri 2 Wonogiri. The study was a descriptive qualitative research. This study was used (1) to obtain a comprehensive view and depth of the problems investigated in accordance with the realities of the educational unit of SMK Negeri 2 Wonogiri, and (2) close linkage with management of the interaction process elements in it so that the required research methods an emphasis on description, induction, background theory and analysis to the understanding of individuals involved in the process. The design of this research is ethnography. Ethnography is one model that more research related to anthropology, which studies cultural event, which presents a view of life that becomes the object of study subjects. Implementation of ISO 9001-2000 QMS in SMK Negeri 2 Wonogiri has the objective that the management in all public schools to be better quality than before implementing ISO 9001-2000 QMS. The entire school community to implement a quality management with full consciousness without any coercion, so that all targeted areas with high quality. All activities such as admission of new students, teaching and learning activities, the administration of teachers, school administration, finance, facilities, student, evaluation and reporting activities, the absorption of out put by the stakeholders can be monitored easily because all meticulously documented.